The Importance of Hadith Studies and the Criteria for Determining Authenticity - Rasyd Ripai Ritonga; Komaruddin Sassi (CV. Creative Tugu Pena, 2025)
This study aims to examine the urgency of Hadith research in the digital era, a period that presents new challenges to the validity and transmission of prophetic traditions. Employing a library research approach, the study analyzes developments in Hadith criticism methodology, the dynamics of fabricated or weak Hadith circulating on social media, and the contribution of Hadith scholarship to strengthening religious understanding in modern society. The findings indicate that low Hadith literacy among the public contributes to the increasing use of unverified narrations, highlighting the need for enhanced educational strategies and religious moderation. The study also emphasizes that the modernization of Hadith methodology must uphold classical epistemological principles while integrating digital technology, including the development of AI-based Hadith research databases. This research contributes theoretically to enriching the literature on Hadith studies and proposes directions for multidisciplinary research aimed at improving religious literacy and mitigating the misuse of Hadith. Its limitation lies in the absence of empirical field verification; thus, future studies are recommended to measure the social impact of unauthentic Hadith circulation on the religious practices of Indonesian Muslim communities